2000
DOI: 10.1016/s0925-4439(00)00086-7
|View full text |Cite
|
Sign up to set email alerts
|

Does ethanol metabolism affect erythrocyte hemolysis?

Abstract: The effects of ethanol and acetaldehyde on the hemolytic stability of rabbit erythrocytes have been compared. Incubation of normal erythrocytes with ethanol facilitated both acidic and oxidative hemolysis and increased the percentages of cells that were hemolyzed at maximal rate. Acetaldehyde exerted a similar destabilizing effect on erythrocytes only in the case of oxidative hemolysis. The destabilizing effect of ethanol was observed in catalase-inactivated erythrocytes under acidic, but not oxidative, hemoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The reported antioxidant effects of EGb 761 have been observed usually in tissues either from pathological conditions or subjected to peroxidative stress Dogan, 1995a, 1995b;Pietri et al, 1997;Seif-El-Nasr and El-Fattah, 1995), whereas in the present study the oxidative effect of EGb 761 was observed in the tubes that were not exposed to H 2 O 2 . A similar TBARS increasing effect of directly applied vitamin E was also seen but it can be attributed to the oxidative haemolysis facilitating effect of its vehicle, absolute ethanol (Tyulina et al, 2000).…”
Section: Discussionmentioning
confidence: 53%
“…The reported antioxidant effects of EGb 761 have been observed usually in tissues either from pathological conditions or subjected to peroxidative stress Dogan, 1995a, 1995b;Pietri et al, 1997;Seif-El-Nasr and El-Fattah, 1995), whereas in the present study the oxidative effect of EGb 761 was observed in the tubes that were not exposed to H 2 O 2 . A similar TBARS increasing effect of directly applied vitamin E was also seen but it can be attributed to the oxidative haemolysis facilitating effect of its vehicle, absolute ethanol (Tyulina et al, 2000).…”
Section: Discussionmentioning
confidence: 53%
“…In fact, the ethanol causes several haemolytic disorders due to both direct and indirect effects [13]. Additionally, the ethanol metabolite acetaldehyde inside of the erythrocyte has the ability to generate free radical species and to cause deleterious effects on erythrocytes [26]. Although several effects of the ethanol and its metabolites on erythrocytes have been reported previously, there has been no report to analyse its effects on erythrocyte CA enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…24-48 hours after ingesting foods like fava beans, characteristic symptoms occur in the form of pallor, jaundice and hemoglobinuria (Ninfali, et al, 2000). In addition, jaundice, headache, backache, nausea, fever, and chills are all signs of acute hemolysis (Tyulina, et al, 2000). Favism is most common seen in children between the ages of 2-5, and is also 2-3 times more common in boys than in girls (Luzzatto, 2001).…”
Section: 5mentioning
confidence: 99%